Hydrocarbon Load and The Occurrence of Diverse Species of Pseudomonads in Ibeno Wetland Soil, Southern Nigeria - Obot, U. R.; Adegoke A. A.; Abraham, N.; Akinjugula, O. J; Essien, J. P; Etok, C. A (American Journal of Biology and Natural Sciences, 2026)
The degradation of hydrocarbon by indigenous biosurfactant-producing species of pseudomonas stands out as a natural remediation phenomenon in the Ibeno coastal soils. Standard microbiological and biotechnological methods were employed to investigate the bioremediation of hydrocarbon in Ibeno coastal soil using an indigenous strain of biosurfactant-producing Pseudomonas aeruginosa. The Physicochemical analysis of the soil included the determination of pH, total organic carbon available phosphorus, total organic nitrogen exchangeable cations, exchangeable acidity, particle size, total petroleum hydrocarbon petroleum aromatic hydrocarbon load, availability of heavy metals, density of heterotrophic bacteria and hydrocarbon utilizing bacteria. The study revealed a slightly acidic soil that is predominantly sandy (with a mean sand fraction of 87.47%, followed by 9.81% clay and 2.2% silt) but, poor in nitrogen and phosphorus contents. However, the results of the microbial analysis showed that the Ibeno coastal soil has a high heterotrophic status with a mean total heterotrophic bacterial (THB) count of 7.9 x104 CFU/g with only 1.9 x102CFU/g (0.024 %) of the heterotrophs (HUB) endowed with the ability to utilize hydrocarbon. Pseudomonads were also detected and their densities in the coastal soil ranged from 5.6 x 103CFU/g to 6.0 x 103 CFU/g. These included; Pseudomonas cepacia, P. putida, S. maltophila, P. aeruginosa, P. flourescens, P. diminuta and P. stutzeni. Amongst the isolates, P. aeruginosa and P. flourescens with percentage occurrence rates of 100% and 75% respectively, were the major occurring pseudomonas species isolated from Ibeno coastal soil. The available Pseudomonads augment the Ibeno coastal soil by the production of biosurfactants.